Are Models of Multilingualism Transferable from Western to Central/Eastern European Contexts? - Hogan-Brun, Gabrielle (Kalbotyra, 2006)
The study of multilingualism is becoming ever more urgent as the ongoing rise in the rate of migration into and across Europe increasingly adds to existing levels of language diversity and contact in Europe. Critically examining the diverging sociolinguistic settings in Western and Central/Eastern Europe, this paper discusses issues pertaining to the transferability of models of multilingualism. It argues that language management practices need to involve critical analyses of language in society that take into account the historic conditions of language (ideological) contexts.